Cognitive Neuroscience Perspectives on Motivation and Learning: Revisiting Self‐Determination Theory. Issue 1 (7th December 2020) - Luria, Ela; Shalom, Maya; Levy, Daniel A.
ABSTRACT: The Self‐Determination Theory of motivation (SDT) has significantly guided educational policy and research. It maintains that learning succeeds when brought about by autonomous rather than controlled motivation, and that extrinsic reward motivation cannot engender effective learning. We present an alternative approach, rooted in recent insights from the neurobiology of memory. In exploring environments to reap rewards, people pursue interrogative goals, accompanied by dopamine‐based hippocampus activation, leading to the formation of rich relational memories. In contrast, seeking to avoid punishment or loss involves imperative goals, with amygdala activation driving the perirhinal cortex to form disjoint item memories. We suggest that structuring learning and evaluation to diminish failure and increase repeated opportunities for successful performance, as in gamification, may engender effective learning incorporating broad perspectives and rich associations. This may occur even in the absence of intrinsic motivation to master a particular subject. Employing this insight in instructional design may benefit many educational frameworks. Abstract : Lay abstract: The Self‐Determination Theory of motivation vigorously promotes learning through autonomous‐intrinsic (vs. controlled‐extrinsic) motivation. We present an alternative approach, based on insights about differences between learning processes engendered by interrogative reward exploration goals, involving the dopamine‐hippocampus‐based formation of rich relational memories, and imperative loss avoidance goals, involving the amygdala‐perirhinal cortex‐based formation of disjoint item memories. We propose that structuring learning and evaluation to diminish failure and afford multiple success opportunities, as in gamification, may engender highly effective learning.